IMPROVING STUDENTS' WRITING ACHIEVEMENT THROUGH THE IMPLEMENTATION OF MIND MAPPING STRATEGY INTEGRATED WITH STAR CHART FOR GRADE EIGTH OF CLASS B2 STUDENTS AT SMPN 4 SINGARAJA IN THE ACADEMIC YEAR 2013/2014 - ., Gusti Agung Ayu Inten Ariprami; ., Drs.Sudirman, M.L.S; ., Nyoman Karina Wedhanti, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini merupakan penelitian tindakan kelas yang bertujuan untuk (1) mengetahui apakah strategi Mind Mapping yang diintegrasikan dengan Star Chart dapat meningkatkan prestasi menulis siswa, (2) mengetahui tanggapan siswa mengenai pengimplementasian strategi tersebut. Penelitian ini dilakukan dalam dua siklus yang terdiri dari tiga sesi di setiap siklusnya. Penelitian ini menggunakan dua jenis data (data kualitatif dan quantitatif) yang dikumpulkan melalui tes, kuisioner, dan buku harian peneliti Hasil tes menunjukan bahwa prestasi siswa meningkat di setiap siklusnya. Nilai rata-rata siswa di pre-test ialah 63.75, 69.79 di posttest 1, lalu meningkat menjadi 80.11 di posttest 2. Peningkatan tersebut dapat dilihat melalui jumlah siswa yang lulus: 3 siswa di pretest, 12 siswa di posttest 1, dan 25 siswa di post test 2. Hasil dari kuisioner dan buku harian peneliti menunjukan bahwa siswa memberikan tanggapan yang sangat positif terhadap pengimplementasian strategi Mind Mapping dan Star Chart.Kata Kunci : Strategi Mind Mapping, Star Chart, Prestasi Menulis, Teks Recount This study was a classroom based action research which aimed to (1) find out whether Mind Mapping strategy which is integrated with Star Chart can improve students’ writing achievement, (2) find out the response of the students toward the implementation of the strategies. This study was conducted in two cycles consisting of three sessions in each cycle. There were two kinds of data (qualitative and quantitative data) which were collected through tests, questionnaires, and writer’s diary. The result of the tests showed that the students’ writing achievement was improved in each cycle. The students’ mean score was 63.75 in pre test, 69.79 in post test 1, and improved became 80.11 in post test 2. It can be seen on the number of students passing the test. There were 3 students passed in the pre test, 12 students in the post test 1, and 25 students in the post test 2. The result of questionnaire and writer’s dairy showed that the students gave positive response toward the implementation of Mind Mapping strategy and Star Chart. The results of the questionnaires showed that 25 (89.29%) of the students admitted that they really like the implementation of Mind Mapping strategy and Star Chat. Moreover, 27 (96.43%) of the students admitted that they were motivated in learning English using Mind mapping strategy and Star Chart.keyword : Mind Mapping Strategy, Star Chart, Writing Achievement, Recount Text